Unveiling the mechanisms of factor flows in enhancing rural multi-dimensional values: a case study of Hunan Province, China - Liu, Qing; Zhao, Ru; Ren, Hui; Tian, Lianghui; Xie, Qiuyu (Frontiers in Sustainable Food Systems, 2025)
The reconstruction of the rural multi-dimensional values of the countryside in the context of factor mobility is a key path to promote the integrated development of urban and rural areas. A dynamic panel model and a spatial Durbin model were employed to analyze the synergistic, agglomeration, and spillover effects of four key factors—population, capital, information, and technology—on the evolution of rural diverse values, with a focus on Hunan Province. The primary conclusions of the study are as follows: (1) A substantial synergistic effect exists among the factors, with the driving effect strengthening as interactions increase; the strongest synergy occurs when all four factors interact. (2) Factor mobility exhibits clear spatial agglomeration effects, reinforcing resource concentration in advantageous regions and reshaping internal value distribution within those regions. (3) Factor mobility also shows significant spatial spillover effects, where elements in core regions positively influence the enhancement of rural diversified values in surrounding areas. (4) The synergistic effects of these elements establish the value foundation, agglomeration effects form growth poles, and spillover effects drive regional linkage. The synergy of these three effects collectively effects the trajectory for enhancing rural value. This study contributes to the advancement of understanding regarding how factor flows promote rural value enhancement and offers empirical evidence to inform optimized allocation of urban-rural factors and policies for rural revitalization in Hunan Province.